Acute kinematic adaptations to running on a centrifugal track: A pilot study. (September 2018) - Picerno, Pietro; Padulo, Johnny
The centrifugal track, a basin-shaped track characterised by a platform with a parabolic section, exploits the centripetal acceleration to increase the bodyweight of the athlete during the foot contact phase of running. Because this overload is produced by an inertial force that is equally distributed to the infinitesimal point masses of the body, no postural changes are expected with respect to level running. This pilot study aimed to compare some selected key kinematic quantities of running on the centrifugal track with respect to level running. A video-based three-dimensional (3D) motion analysis was performed on five sprinters and used to compute spatio-temporal variables, frontal and sagittal trunk kinematics and knee sagittal kinematics at footstrike, midstance and foot-off over two consecutive steps at similar speeds. No significant changes were found in spatio-temporal variables and knee kinematics between the right and the left leg during running on the centrifugal track. Neither step length nor step duration was found statistically different between the two running typologies. Trunk flexion was not altered during the stance phase of running on the centrifugal track. Knee angle at footstrike was found similar to level running. A slightly larger but statistically significant knee flexion at midstance and knee extension at foot-off were found with respect to flat-track running, but these findings appear more beneficial for strength training rather than detrimental for the running technique. The centrifugal track was found to be a viable alternative to the common resisted sprint training techniques as the training effect is produced without localised overloads on the musculoskeletal system and detrimental postural changes.